Nanoparticles as novel plant growth promoters - Adel K. Madbouly (Novel Research in Microbiology Journal)
Crop plants are prone to infection by several pathogens which cause diseases that affect the production and economy of these crops. Farmers tend to use traditional control methods such as; chemical pesticides and bioagents which are non-ecofriendly and not easily produced/ applied, respectively. Nanoparticles (NPs) have sizes less than 100 nm and are considered for several applications including; agriculture, food technology, pharmaceuticals in addition to protection of environment (Chakravarty et al., 2015). Availability, low-cost and nonphytotoxicity of NPs are the main prerequisites for their application in the field of agriculture. Shankramma et al., (2016) added that crop production can be considerably enhanced by the use of suitable growth promoting substances such as nanofertilizers. Recently, Liu et al., (2016) suggested that engineered nanofertilizers can be manipulated for effective utilization of some soil nutrients by the plant such as inorganic phosphorous (P) and water to increase crop productivity.